(untitled) (Global Journal of Science Frontier Research, 2020)
Van der Waals interactions are dipole-dipole interactions. In this article, we study the quantum information storage using repulsive van der Waals interaction coupled states. It is shown that if one atom is excited, the second excited atom will be able to change the state distribution of the first excited atom. This can be used to do remote control at the quantum level. In addition, by analyzing the components of the first excited atom, the distance between the two excited atoms and the state distribution of the second excited atom can be extracted. Such systems are essential for developing single-atom quantum sensors.